2019
DOI: 10.1088/1755-1315/293/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Physiology and genotyping of adaptive and sensitive oil palm progenies under unwatered stress condition

Abstract: Increasing of dry areas for Oil Palm plantation due to climate change led the breeders to develop drought stress, tolerant palm. Characterization of genetic materials for their physiological and genetic properties is required. Two distinct progenies derived from Tanzanian origin used for more adaptive to unwatered stress, and Nigerian origin used for more sensitive, were subjected for analysis. Physiological related variables were observed for sap flow, water potential, soil water content, greenhouse temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Palm response to drought stress is complex from a genomic perspective (Blum 2011;Xiong et al 2006). Oil palm breeders have been trying to discover molecular markers for better drought-tolerant oil palm selection (Wang et al 2020;Yono et al 2019). In the root system, some mechanisms for abscisic acid (ABA) signal production begins that are triggered by rhizosphere water deficit.…”
Section: Discussionmentioning
confidence: 99%
“…Palm response to drought stress is complex from a genomic perspective (Blum 2011;Xiong et al 2006). Oil palm breeders have been trying to discover molecular markers for better drought-tolerant oil palm selection (Wang et al 2020;Yono et al 2019). In the root system, some mechanisms for abscisic acid (ABA) signal production begins that are triggered by rhizosphere water deficit.…”
Section: Discussionmentioning
confidence: 99%
“…Two SNP markers were located in the aquaporin NIP1-1 gene, related to water translocation between cells. One SNP marker was located in the glutamate receptor gene, which is related to glutamate release and proline biosynthesis [ 24 ]. Furthermore, expression data for all transcripts in both progenies demonstrated that numerous genes were expressed differentially, such as genes involved in primary hormone responses, DNA replication and repair, chromatin remodeling, and RNA-mediated DNA methylation.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the initial stages are underway of creating mOP resistant to inclement climates and the ability to combat BSR [36][37][38]. Resistant OP may overcome unfavorable growth conditions [39]. Zhou et al [26] detected the myeloblastosis (MYB) gene family in OP, the largest and most abundant transcription factor families in plants, which have vital roles in development, abiotic stress response, hormone signal transduction, and secondary metabolite regulation.…”
Section: Introductionmentioning
confidence: 99%